Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils F.; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Frontiers in Education, 2021)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots may assist young children in their learning across various fields, the common aim of approaches incorporating social robots in educational practices is typically to supplement the educational process rather than to replace the human caregiver, e.g. the teacher, parent, educator or therapist. However, given this preferable configuration, there is surprisingly little research that pays explicit attention to the caregiver, systematically examining the ways in which children involve or check in with them during the child’s interaction with a robot or exploring similarities and differences between children’s interaction behavior with robots compared to human partners. In the present study, we observed 20 preschool children aged 4 to 5 years over 4 sessions in our laboratory and investigated how the children involved their caregiver over the course of a long-term language learning study. Children were assigned to either an interaction with a social robot or a human partner. Linking to the phenomenon of social referencing, we analyzed how often the children referred to their caregiver. Our results revealed that all children involved in the experimental interactions addressed their caregiver. However, we found that the children who interacted with the social robot involved their caregiver significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analysis showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with reference to the caregiver’s role during children’s interactions with social robots and the implications for future interaction design.